2021
DOI: 10.3960/jslrt.20040
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution after T-cell replete HLA haploidentical hematopoietic stem cell transplantation using high-dose post-transplant cyclophosphamide

Abstract: As HLA haploidentical related donors are quickly available, HLA haploidentical hematopoietic stem cell transplantation (haploHSCT) using high-dose post-transplant cyclophosphamide (PTCy) is now widely used. Recent basic and clinical studies revealed the details of immune reconstitution after T-cell replete haploHSCT using PTCy. T cells and NK cells in the graft proliferate abundantly at day 3 post-haploHSCT, and the PTCy eliminates these proliferating cells. After ablation of proliferating mature cells, donor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…T-cell-memory phenotype skewing and inverted CD4/ CD8 ratio persisted until 5 months post-HCT. These posttransplant lymphocyte reconstitutions were similar to previous reports (24)(25)(26)(27)(28). Particularly, the rapid expansion of NK cells may be partly caused by comorbid CMV infections, and delayed T-cell reconstitution may have been affected by the relatively high dose of alemtuzumab in our case.…”
Section: Immune Reconstruction After Hctsupporting
confidence: 91%
“…T-cell-memory phenotype skewing and inverted CD4/ CD8 ratio persisted until 5 months post-HCT. These posttransplant lymphocyte reconstitutions were similar to previous reports (24)(25)(26)(27)(28). Particularly, the rapid expansion of NK cells may be partly caused by comorbid CMV infections, and delayed T-cell reconstitution may have been affected by the relatively high dose of alemtuzumab in our case.…”
Section: Immune Reconstruction After Hctsupporting
confidence: 91%
“…A recent meta-analysis showed that PTCy regimen versus ATG in allo-HSCT from unrelated donors was associated with a lower chance of developing EBV-related PTLD disease [36]. In the PTCy conditioning regimen, cyclophosphamide targets proliferating cells as NK and CD8+ T cells, but maintains CD4+ T cells in significant numbers compared to ATG, which could confer a clinical advantage to PTCy in maintaining control of EBV reactivation [37][38][39].…”
Section: Incidence Of Ebv-dnaemia After Allogeneic Hsctmentioning
confidence: 99%
“…In pediatric patients, adenovirus and cytomegalovirus remain frequent causes of transplant-related mortality [1][2][3][4][5][6][7][8] . While new approaches of HSCT such as αβT cell receptor (TCR) depletion or the use of post-transplant cyclophosphamide have expanded potential donor pools [9][10][11] , these approaches cause delayed T cell reconstitution 12,13 , impairing critical antiviral defenses 14 .…”
mentioning
confidence: 99%